Expression of E-selectin ligands on circulating tumor cells: cross-regulation with cancer stem cell regulatory pathways? - Burdick, Monica M.; Henson, Karissa A.; Delgadillo, Luis F.; Choi, Young Eun; Goetz, Douglas J.; Tees, David F.; Benencia, Fabian (Frontiers in Oncology, 2012)
Although significant progress has been made in the fight against cancer, successful treatment strategies have yet to be developed to combat those tumors that have metastasized to distant organs. Poor characterization of the molecular mechanisms of cancer spread is a major impediment to designing predictive diagnostics and effective clinical interventions against late stage disease. In hematogenous metastasis, it is widely suspected that circulating tumor cells (CTCs) express specific adhesion molecules that actively initiate contact with the vascular endothelium lining the vessel walls of the target organ. This “tethering” is mediated by ligands expressed by CTCs that bind to E-selectin expressed by endothelial cells. However, it is currently unknown whether expression of functional E-selectin ligands on CTCs is related to cancer stem cell (CSC) regulatory or maintenance pathways, particularly epithelial-to-mesenchymal transition (EMT) and the reverse, mesenchymal-to-epithelial transition (MET). In this Hypothesis and Theory article, we explore the potential roles of these mechanisms on the dynamic regulation of selectin ligands mediating CTC trafficking during metastasis.